LIVING HADIS DALAM KULTUR PENDIDIKAN TINGGI PESANTREN: STUDI KASUS PADA MA’HAD ALY HASYIM ASY’ARI TEBUIRENG - Khasani, Fahim (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
Pesantren is a place for students to build good character and study Islamic sciences deeply. The Traditions enforced in Pesantren for many years have moral values inspired by the hadith of the Prophet. Phenomena like this is part of the study of living hadith, which is an effort to gain knowledge about the culture, thoughts, behavior and traditions of the people inspired by the hadith of the Prophet. Ma'had Aly Hasyim Asy'ari is the center for hadith studies at the Tebuireng Islamic Boarding School. Ma'had Aly known as a special higher education institution based on Islamic boarding schools (pesantren) that teaches Islamic sciences. It was founded with the intention of producing qualified religious scholars, particularly in the discipline of Hadith. To achieve this goal, campus management implements a measurable academic culture. This study uses qualitative methodologies to examine the academic culture which is a manifestation of the practice of living hadith, how it is implemented and the results achieved after implementing this academic culture.